Essencialidade ambiental e tributação extrafiscal no imposto sobre produtos industrializados - Marchi, Cristiane de (2017)
In the current severe global environmental crisis, caused mainly by the human activity, as a result of predatory, unbridled and irrational economic growth, the principle of sustainability determines a new order of dynamic rebalancing, interconnecting, for example, the spheres of taxation and sustainable development. It is a question of systematic reinterpretation of the constitutional norms, since the existence of an ecologically balanced right to the environment (essential to healthy quality of life - Article 225, CF) requires differentiated treatment according to the environmental impact of products and services and their processes of elaboration and delivery (Article 170, VI, CF). It is, therefore, necessary to revise the tax categories so that they align with the controls in question. The Extra-fiscal taxation certainly constitutes one of the mechanisms capable of carrying out a regulatory task of modulating the conduct of economic agents, based on environmental prevention duties, so as to avoid, in a diligent, efficient and effective manner, the causal link of predictable damages. In this context, the Tax on Industrialized Products (Article 153, I and §3º, CF), especially for its explicit constitutional obligation to be selective in function of the essentiality of the product, as well as for its strong extra-fiscal character, is crucial because it affects all stages directly affecting the environment, from the elaboration process to the actual use of the industrialized product (consumption), as well as its disposal. For these reasons, the re-reading of IPI proposed here, in the light of constitutional system, is in the sense that the selectivity, due to the essentiality, deserves to be rethought and understood from the point of view of the defense of sustainability and the ecologically balanced environment. The IPI taxation, from this perspective, can occur in various ways, examined in this dissertation, all those conducive to sustainable behavior.